RIFM fragrance ingredient safety assessment, 4-(p-hydroxyphenyl)-2-butanone, CAS Registry Number 5471-51-2. (December 2019) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Abstract: The existing information supports the use of this material as described in this safety assessment. 4-(p-Hydroxyphenyl)-2-butanone was evaluated for genotoxicity, repeated dose toxicity, developmental and reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data show that 4-(p-hydroxyphenyl)-2-butanone is not genotoxic. Data on 4-(p-hydroxyphenyl)-2-butanone provide a calculated MOE >100 for the repeated dose toxicity endpoint. The developmental and reproductive toxicity and local respiratory toxicity endpoints were evaluated using the TTC for a Cramer Class I material, and the exposure to 4-(p-hydroxyphenyl)-2-butanone is below the TTC (0.03 mg/kg/day and 1.4 mg/day, respectively). Data from 4-(p-hydroxyphenyl)-2-butanone show that there are no safety concerns for skin sensitization under the current declared levels of use. The phototoxicity/photoallergenicity endpoints were evaluated based on UV spectra; 4-(p-hydroxyphenyl)-2-butanone is not expected to be phototoxic/photoallergenic. The environmental endpoints were evaluated; 4-(p-hydroxyphenyl)-2-butanone was found not to be PBT as per the IFRA Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., PEC/PNEC), are <1. Highlights: 4-( p- Hydroxyphenyl)-2-butanone; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.